Effect of rib fat thickness on the quality of aged meat from Nellore young bulls - Dallantonia, Erick Escobar [UNESP]; Lage, Josiane Fonseca; Simonetti, Laís Regina [UNESP]; Vito, Elias San [UNESP]; Delevatti, Lutti Maneck [UNESP]; Berchielli, Telma Teresinha [UNESP] (Editora da Universidade Estadual de Maringá - EDUEM, 2015)
This trial aimed to evaluate the quality of aged beef from Nellore young bulls under two yield grade (YG). Fourteen animals with approximately 450 ± 30 kg body weight were evaluated for backfat thickness (BFT) at the beginning of the experimental period. Seven animals had BFT of 0-3 mm and seven animals, 3.1-6 mm. Two groups were formed at the end of the experiment: animals finished with 3-6 mm BFT (seven animals) and animals finished with 6.1 to 10 mm BFT (seven animals). Every 28 days, we evaluated by ultrasound the BFT between the 12nd 13rd ribs. There was no interaction between YG and aging for beef color, pH, cooking losses and shear force (p > 0.05). There was no effect of YG on sarcomere length (p = 0.11). However, there was interaction between YG and aging on water holding capacity (p < 0.01). The yield grades evaluated did not interfere with meat quality, but carcasses with 6.1 - 10 mm of backfat thickness showed highest water holding capacity. The aging of the longissimus muscle for up to 14 days improves beef tenderness.

Objetivou-se neste trabalho avaliar a qualidade da carne maturada de tourinhos Nelore, sob dois graus de acabamento (GA) de carcaça. Foram utilizados 14 animais, com aproximadamente 450 ± 30 kg de peso corporal. A espessura de gordura subcutânea (EGS) dos animais foi avaliada no início do período experimental. Foram escolhidos 14 animais com EGS de 0-3 mm e 3,1-6 mm, formando-se dois grupos ao final do experimento: animais com acabamento entre 3-6 mm (sete animais) e entre 6,1-10 mm (sete animais). A cada 28 dias foram avaliados a EGS entre a 12-13ª costelas com ajuda de unidade ultrassonográfica. Os valores de coloração da carne, pH, perdas por cocção e força de cisalhamento não tiveram efeito de interação entre os tratamentos (p > 0,05). Não houve diferença significativa entre o GA sobre o comprimento de sarcômero (p = 0,11). Houve interação entre GA e maturação sobre a capacidade de retenção de água (p < 0,01). Os graus de acabamento avaliados não interferem na qualidade da carne, mas carcaças com acabamento entre 6,1-10 mm apresentam maior capacidade de retenção de água. A maturação do músculo longissimus em até 14 dias melhora a maciez da carne.
Efeito da espessura de gordura subcutânea sobre a qualidade da carnematurada de tourinhos da raça Nelore
Keywords: aging; longissimus; subcutaneous fat; maturação; longissimus; gordura subcutânea